TRADING RULES OR TRADING VALUES? AFTA–CHINA DISPUTE MECHANISMS UNDER POSITIVE LAW VS. ISLAMIC LAW & WHAT INDONESIA MUST DECIDE - Maryani, Halimatul; Susilo, Adhi Budi; Lateef, Owoade Abdul (Jurnal Pembaharuan Hukum, 2024)
In principle, Indonesia likes it or not, willingly or unwillingly, now Indonesia has joined the ASEAN China Free Trade Agreement which of course has an international trade system as its outlet. This means that Indonesia and the countries involved in this agreement are free to conduct international relations, including international trade. The research method used in this study is the Normative juridical method which examines legal issues while providing a descriptive perception of what should be, using the statute approach and the conceptual approach. The purpose of this study is to examine the principles of resolving regional trade disputes between Afta and China from the perspective of positive law and Islamic law and their implications for Indonesia. As an innovation, the findings offered in this presentation are that there are principles for resolving regional trade disputes between Afta and China from the perspective of positive law and Islamic law and their implications for Indonesia, both in the provisions of the WTO, Afta China, and also the principles in the provisions of Islamic law, remain in line with the provisions applicable in the WTO.